The Relationship Between Ovarian Cancer Stage and Histopathology Features in Operated Patients at Dr.Zainoel Abidin General Public Hospital in Banda Aceh, Indonesia - Hasanuddin; Rizka Aditya; Pasca, Cindy Swara (Journal of International Surgery and Clinical Medicine, 2025)
Introduction: As the fourth leading of cancer death among worldwide for women, cancer of ovary remains a serious public health issue. Late-stage diagnosis is common and significantly reduces the 5-year survival rate—from 92% in early stages to just 17%–28% in advanced cases.  Unspecific symptoms of ovarian cancer cause most patients to present at an advance stage. Histopathology plays a role in diagnosis, prognosis, and decision-making for patient management. Recognizing histopathology early on helps direct therapy and improve patient outcomes. To date, however, no researches have been established on the relationship between ovarian cancer stage and histopathology type at Dr. Zainoel Abidin General Hospital Banda Aceh, Indonesia. Methods: This study utilized a retrospective cross-sectional design, gathering data from medical records from patients with cancer of ovary treated between January and December 2024. Statistical analyses, including univariate and bivariate tests, were conducted using the Kruskal-Wallis method and SPSS version 26.0 Result: Analysis of the relationship between surgical stage and histopathological features revealed a statistically significant correlation, with a p-value of 0.000. Conclusion: Surgical staging can be considered when developing appropriate therapeutic strategies while awaiting histopathology results. This allows patients to receive treatment as soon as possible.